1989
DOI: 10.1152/ajpgi.1989.256.4.g704
|View full text |Cite
|
Sign up to set email alerts
|

Ability of prostaglandin to reduce ethanol injury to dispersed chief cells from guinea pig stomach

Abstract: To determine whether prostaglandin exerts a direct action on individual gastric epithelial cells that protects them from ethanol-induced injury, dispersed chief cells from guinea pig stomach were pretreated with 16,16-dimethyl-prostaglandin E2 (dmPGE2) or placebo before incubation with ethanol or control. Cell injury was assessed in terms of exclusion of Fast Green dye, release of lactate dehydrogenase, alterations of ultrastructure, and pepsinogen secretion stimulated by a variety of secretagogues. Of chief c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Nonsteroidal anti-inflammatory drugs (NSAIDs) aggravate ethanol-caused gastric damage, 15,16 and it is well known that endogenous PGs may contribute to the mucosal defense mechanism by minimizing the damage. [17][18][19][20][21][22][23][24][25] We also found, in the present study, that NS-398, a selective COX-2 inhibitor, aggravated the 95% ethanol-caused gastric damage only in mice pretreated with acidified ethanol that showed COX-2 protein expression. These effects of NS-398 were similar to NSAID effects shown previously.…”
Section: Discussionsupporting
confidence: 72%
“…Nonsteroidal anti-inflammatory drugs (NSAIDs) aggravate ethanol-caused gastric damage, 15,16 and it is well known that endogenous PGs may contribute to the mucosal defense mechanism by minimizing the damage. [17][18][19][20][21][22][23][24][25] We also found, in the present study, that NS-398, a selective COX-2 inhibitor, aggravated the 95% ethanol-caused gastric damage only in mice pretreated with acidified ethanol that showed COX-2 protein expression. These effects of NS-398 were similar to NSAID effects shown previously.…”
Section: Discussionsupporting
confidence: 72%
“…This PG action, which seems to be independent of their inhibitory action on gastric acid secretion, is referred to as cytoprotection (7). However, in addition to the mechanisms proposed, recently available evidence has suggested that PGs may also preserve the viability of not only gastric glands but also a homogeneous population of gastric cells exposed to noxious agents in vitro (8)(9)(10). Because PGs can directly interact with and protect gastric cells in the absence of mucus, blood flow, or bicarbonate, it is reasonable to speculate that PGs exert their protective effects presumably through activating intracellular processes.…”
mentioning
confidence: 99%
“…Because of these biological activities, PGE 1 and some of its analogues have been reported effective for treatment of obstructive diseases in various organs, including ischemic retinopathy (Heffelfinger et al 1987;Zygulska-Mach et al 1980;Carlson and Olsson 1976). Recent studies have shown that some types of prostaglandins, including PGE 1 , have cytoprotective activity against various noxious agents, ethanol, and taulocholic acid in cultured gastric cells (Cherner et al 1989;Tarnawski et al 1988;Lancaster and Robert 1978). On the basis of these findings, we hypothesized that, in ischemic retinopathy, PGE 1 may function as a tissue protector, accompanied by induction of ADF.…”
mentioning
confidence: 99%